Stroke parameter analysis performing a competition distance (200m) on water - Veispals, M.; Gulbe, A. (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, Volume II, May 26th, 2023, 2023)
Canoe sprint is a water sport (under natural conditions, it takes place on water); therefore, for the most part, research is carried out under laboratory conditions, when the load is performed on various special exercise machines (ergometers) that try to simulate natural conditions as closely as possible since doing research in natural conditions is very challenging. However, technological development and recently available specific devices allow to go forward and overcome these challenges. The aim of the research is to provide information on stroke parameters for a 200 m distance with maximum effort in natural conditions of the sport - on water, provided by the only device currently available on the market that measures the power and force applied to the stroke, and result comparison with similar research done by other authors. Dynamometry was used as the primary method to obtain indicators on power and force applied to the paddle, using a specialized device - canoe sprint power meter (One Giant Leap, Nelson, New Zealand). The average force value to the brace in a 200 m distance between all 87 braces was found to be 456.2 ± 8.7 N.